Influence of game format and team strategy on physical and perceptual intensity in soccer small-sided games - Guard, A.; McMillan, K.; MacFarlane, N. (International Journal of Sports Science & Coaching, 2022)
The aim of the study was to compare internal and external load responses of different small-sided games, using balanced (5v5 Possession and small-sided games formats) and unbalanced (6v4) teams. Ten elite youth male soccer players were monitored at the start of the in-season period using global positioning system, heart rate and subjective ratings of intensity. Results showed higher physiological stress (>90% HRmax) in Possession and small-sided games formats when compared to the unbalanced teams (ES = 1.3-2.3). Total and high-intensity distance in small-sided games (28 ± 25 m) and Possession (67 ± 35 m) were greater compared to teams of 6 and 4 in the unbalanced scenario. Small-sided games format and team with six players had higher proportion of distance running at sub-maximal velocities (0-5.8 m/s2). Small-sided games format and team with four players saw greater mean acceleration effort (mean acceleration intensity in small-sided games 1.91 ± 0.27 vs. Possession 1.80 ± 0.20 m/s2, ES = 0.4 and Team 4 1.56 ± 0.24 vs. Team 6 1.44 ± .0.19 m/s2, ES = 1.3). Small-sided games format and team with 6 players had lower starting velocities prior to acceleration efforts (small-sided games 0.90 ± 0.08 and Team 6 1.11 ± 0.11 m/s2, ES = 1.5 and ES = 1.8), while velocity at the end of each acceleration effort was greater in the Possession format and Team 4 compared to small-sided games and Team 6 (Possession 3.54 ± 0.23 m/s2 and Team 4 3.13 ± 0.22 m/s2) compared to the small-sided games format (ES = 0.1) and the team with six players (ES = 2.3). These data demonstrate that using unbalanced teams can provide an additional form of training prescription to facilitate player specific training within a squad environment by providing different internal and external training responses within a combined drill.